The DNA Methyltransferase 1 (DNMT1) Controls the Shape and Dynamics of Migrating POA-Derived Interneurons Fated for the Murine Cerebral Cortex. (22nd November 2016) - Pensold, Daniel; Symmank, Judit; Hahn, Anne; Lingner, Thomas; Salinas-Riester, Gabriela; Downie, Bryan R; Ludewig, Fabian; Rotzsch, Anne; Haag, Natja; Andreas, Nico; Schubert, Katrin; Hübner, Christian A; et al.
Abstract: The proliferative niches in the subpallium generate a rich cellular variety fated for diverse telencephalic regions. The embryonic preoptic area (POA) represents one of these domains giving rise to the pool of cortical GABAergic interneurons and glial cells, in addition to striatal and residual POA cells. The migration from sites of origin within the subpallium to the distant targets like the cerebral cortex, accomplished by the adoption and maintenance of a particular migratory morphology, is a critical step during interneuron development. To identify factors orchestrating this process, we performed single-cell transcriptome analysis and detected Dnmt1 expression in murine migratory GABAergic POA-derived cells. Deletion of Dnmt1 in postmitotic immature cells of the POA caused defective migration and severely diminished adult cortical interneuron numbers. We found that DNA methyltransferase 1 (DNMT1) preserves the migratory shape in part through negative regulation of Pak6, which stimulates neuritogenesis at postmigratory stages. Our data underline the importance of DNMT1 for the migration of POA-derived cells including cortical interneurons.